Effect of Anti-lock Braking System Modulation Frequency on Flywheel-Based Energy Harvesting During Panic Braking - Agung Prijo Budijono; I Nyoman Sutantra; Agus Sigit Pramono; Aris Purwanto; Po-Hung Lin (Universitas Muhammadiyah Magelang, 2026)
A considerable portion of braking energy in electric vehicles is dissipated as heat, especially during severe or panic braking. This study experimentally investigates the effect of anti-lock braking system (ABS) modulation frequency on flywheel-based energy harvesting during panic braking using a laboratory-scale Flywheel Regenerative Capture System (FRCS). The proposed setup integrates an ABS braking unit, a magnetic clutch, a flywheel, and an electrical generator to recover part of the braking energy while maintaining braking stability. Experiments were conducted at ABS modulation frequencies of 10, 20, 30, 40, and 50 Hz. Braking performance was evaluated using wheel-speed response, slip ratio, braking time, braking distance, flywheel rotational response, and generated electrical power. At an initial braking speed of 1000 rpm, the ABS braking process operated within a slip-ratio range of approximately 0.17–0.38, while the shortest braking distance under regenerative braking reached about 15.83 m at 40 Hz, compared with about 19.58 m at 10 Hz without regenerative braking. The 10 Hz setting produced the most stable deceleration pattern, the highest flywheel rotational response, and the highest electrical output, whereas higher frequencies increased fluctuation and reduced effective torque transfer to the generator. These findings indicate that ABS modulation frequency strongly influences both braking stability and flywheel-based energy harvesting performance. The study demonstrates the feasibility of integrating a flywheel regenerative capture system with ABS-controlled panic braking, providing a basis for further vehicle-scale development.